2021
DOI: 10.3389/fcell.2021.725678
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Positive Selection High Throughput Genetic Screen in Dictyostelium discoideum

Abstract: The cellular slime mold Dictyostelium discoideum is a powerful model organism that can be utilized to investigate human health and disease. One particular strength of Dictyostelium is that it can be utilized for high throughput genetic screens. For many phenotypes, one limitation of utilizing Dictyostelium is that screening can be an arduous and time-consuming process, limiting the genomic depth one can cover. Previously, we utilized a restriction enzyme-mediated integration screen to identify suppressors of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Moreover, tenfold more plates must be prepared to analyse tenfold more mutants; hence, it is important to improve the efficiency of selection methods. For selection of REMI and NTG-treated mutants in Dictyostelium , various powerful strategies were applied, including adhesion selection on 10-cm plates, electrotaxis experiments with barcoded microplates, high-throughput growth and development assays that affect lithium and valproic acid, and counterselection with 5-fluoroorotic acid to enrich genes that suppress polyglutamine aggregation 28 , 54 56 . Because these techniques allow for the screening of numerous cells, they are easily adaptable to CRISPR mutant pools with millions of mutants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, tenfold more plates must be prepared to analyse tenfold more mutants; hence, it is important to improve the efficiency of selection methods. For selection of REMI and NTG-treated mutants in Dictyostelium , various powerful strategies were applied, including adhesion selection on 10-cm plates, electrotaxis experiments with barcoded microplates, high-throughput growth and development assays that affect lithium and valproic acid, and counterselection with 5-fluoroorotic acid to enrich genes that suppress polyglutamine aggregation 28 , 54 56 . Because these techniques allow for the screening of numerous cells, they are easily adaptable to CRISPR mutant pools with millions of mutants.…”
Section: Discussionmentioning
confidence: 99%
“…The major considerations to genetic screening are saturation of mutation in the mutant pool and ease of identifying mutation sites. It has been indicated that whole-genome sequencing of multiple strains is not cost effective approach and that loss-of-function mutants identified via REMI rarely result in gain-of-function mutations in genes that suppress the original phenotype 26 28 . Thus, the use of a variety of approaches is advantageous for the genetic screening of Dictyostelium .…”
Section: Introductionmentioning
confidence: 99%
“…One caveat of this screen was that it did not approach genome-wide coverage and additional suppressors of polyQ aggregation in Dictyostelium likely exist. The development of novel screening pipelines will enable genome-wide coverage in future screens, fully elucidating the genes that are essential for suppressing polyQ aggregation in Dictyostelium (Williams et al, 2021).…”
Section: Dictyostelium Is Naturally Resistant To Polyglutamine Aggregationmentioning
confidence: 99%